An Analysis on Organizational Behaviours Model of Intel (M) Corporation - Lim Boon Yik; Daisy Mui Hung Kee; Law Hui Qin; Alshammari Mathil; Mohammad Awais; R. Willy Ananta Permadi; Aman Kelpia (International Journal of Applied Business and International Management, 2019)
Models are frameworks or possible explanations why do people behave as they do at work.1 There are so many models in an organization. Different results across the organizations are caused by different in the models of organizational behaviour. The basic model of this paper is to know more about how organizational behaviour influences the Intel (M) Corporation based on the organizational behaviour model. Furthermore, this paper aims to have insights about the employees in Intel (M) Corporation which will be influenced by surroundings no matter from physically or psychologically including how company facilities and services influences the organizational behaviour in Intel (M) Corporation or the influence of motivation among employee and company performances. This paper contains a phone interview with one of the managers in Intel (M) Corporation, an American multinational technology company with its Malaysia main headquarter located in Penang to get more about the internal issues regarding organizational behaviour in the company such as overcoming of stress, design of a decision and also company culture and structure. Intel (M) Corporation has turned to be a splendid company in its working environment with both internal and external supports received from employees and the community. We will learn about the influences of Organizational Behaviours towards a company community based on Organizational Behaviour models.